2002
DOI: 10.1016/s0006-3495(02)73981-7
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Deformation of Protein Monolayers

Abstract: Globular proteins are peculiar solids that display both local stability of their conformation and the ability to undergo large cooperative changes of shape (conformational changes). If one forces a large deformation of the molecule, such that the structure is necessarily changed, it is not obvious whether the deformed globule can still remain a solid or whether it will melt. Is it possible to plastically deform a protein? Here we investigate this question with a micro-mechanical experiment on a small region (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…It has been reported that small amounts of crosslinking agents lead to chemical softening of the molecules, which results in larger observed deformations for the same load force in studies on plastic deformation of proteins [25]. When the protein-protein interaction due to Brownian fluctuations is considered, the crosslinking agents can lower this interaction, thus leading to smaller viscosity values of protein with crosslinking agents.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that small amounts of crosslinking agents lead to chemical softening of the molecules, which results in larger observed deformations for the same load force in studies on plastic deformation of proteins [25]. When the protein-protein interaction due to Brownian fluctuations is considered, the crosslinking agents can lower this interaction, thus leading to smaller viscosity values of protein with crosslinking agents.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, from the thermal motion of the bead, one can reconstruct the potential and thus the forces on the bead and the molecular contact. In the present case, the Van der Waals attractive force is small [e.g., for a 1-m-diameter bead, F VdW Ϸ 0.7 pN at a separation h ϭ 20 nm, using the Hamaker constant measured in (27): A ϭ 1.0 ϫ 10 Ϫ14 ergs] compared with the elastic response of the DNA tether (F el Ϸ 3 pN for a ss 60 mer at a relative extension of 1; see below); thus, the restoring force that keeps the bead close to the surface is characteristic of the tether. We exploit this circumstance in the data analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This relation has been shown experimentally to remain valid down to contact (24). The penetration depth ␦ is calculated from the incidence angle and the refractive indexes; however, we also perform an independent calibration of the displacement measurements (⌬h) by observing the vertical motion of a free (untethered) bead and comparing the gravitational potential thus obtained to the weight of the bead (23,26,27). The absolute bead-slide separation can also be calibrated by collapsing the bead on the slide surface at the end of the measurement to obtain the contact intensity.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that this protocol allows a quite significant reduction in the time necessary for immobilization compared to a cyano-functionalized mesoporous-based reactor (with a pore diameter of 18 nm) that requires 16 h at room temperature as reported by Quiao and co-workers. [10] To test the proteolytic activity of trypsin in this system, we selected myoglobin, which is known to be a proteolitically resistant substrate; [18] moreover its dimensions (3 4 5 nm) [19] are compatible with the pore opening and diffusion pathways in our materials.…”
mentioning
confidence: 99%